Metabolizable Energy and Amino Acid Digestibility of Soybean Meal from Different Sources for Broiler Chickens Supplemented with Protease - Maurílio de Lucas Xavier Junior; Rafael de Sousa Ferreira; Levy do Vale Teixeira; Jean Kaique Valentim; Kaique Moreira Gomes; Romário Duarte Bernandes; Arele Arlindo Calderano; Luiz Fernando Teixeira Albino (Animals, 2024)
This study investigated the effect of the serine protease on metabolizable energy and amino acids’ digestibility of different soybean meal for broilers. A total of 684 broilers chickens form 14 to 23 d age were distributed with nineteen treatments, six replicates, and six birds per replicate. Nine samples of soybean meal from different regions in Brazil were used, with some samples supplemented with the protease enzyme and others without addition. Apparent and corrected-for-nitrogen-balance metabolizable energy were evaluated, as well as the coefficients of amino acid digestibility. All collected data were submitted to ANOVA at a significance level of 5% and Tukey’s test was applied. The results showed that the addition of the protease enzyme significantly increased the values of AME and AMEn in all soybean meal samples. The soybean meal of different origins has significant variations in AME and AMEn. The addition of the protease improved the digestibility of essential amino acids compared to soybean meal without enzyme addition. These results indicate that supplementation with serine protease can improve the metabolizable energy and amino acid digestibility of soybean meal from different regions in the diet of broilers, potentially being an effective strategy to enhance nutrient utilization and animal performance.